DETECTION OF THE TEA LEAVES WILTING LEVEL WITH DLSI (DYNAMIC SPECKLE LASER IMAGING) NUMERICAL ANALYSIS - Sasmitaninghidayah, Wiwis; Rahmawati, Dian; Mardhiyah, Ainatul (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2025)
This study aimed to find a correlation between the degree of tealight and the speckle image of the tea leaf by using numerical analysis and graphical analysis. Numerical analysis was done using THSP (Time History Of Speckle Patterns), COM (Co-occurrence Matrix), IM (Inertia Moment), and AVD (Average Value of Difference) values. The numbers used in the study showed that THSP and correlation measurements showed changes in the biological activity of tea leaves at all wilting levels. Meanwhile, the IM and AVD values showed significant changes after the tea leaves withered by 57.56%. COM analysis did not show any changes from high to low levels. THSP and correlation measurement showed changes in biological activity in tea leaves. Biological activity was high at high water content, and biological activity decreased as the water content in tea leaves decreased.